ANALISIS PENERAPAN PROSEDUR LOCKOUT DAN TAGOUT (LOTO) SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA DI LINGKUNGAN INDUSTRI MANUFAKTUR - Syaira Zhieka Ramadhani; Anisa Putri Siregar; Nurna Billa; Abdurrozzaq Hasibuan (CV. Adiba Aisha Amira, 2025)
Lockout/Tagout (LOTO) procedure is an essential hazardous energy control method in preventing work accidents during machine maintenance and repair activities in the manufacturing industry. This study aims to analyze the implementation of LOTO as a work accident prevention strategy, by reviewing various studies that have been conducted in the Indonesian manufacturing industry. The results of the analysis indicate that effective LOTO implementation is influenced by factors such as worker knowledge and attitudes, adequate training, and consistent management supervision and policies. Although several companies have adopted the LOTO procedure, challenges such as lack of understanding, limited resources, and non-compliance with the procedure are still encountered. Therefore, ongoing commitment from management and active participation of workers are needed to ensure the effectiveness of LOTO in preventing work accidents.